2014
DOI: 10.1149/2.0211413jes
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Surface Transformations for Photoelectrochemical Energy Conversion

Abstract: The issue of photoelectrode stability, while simultaneously maintaining efficient operation in aqueous solutions, is addressed for energy converting half cells and complete photoelectrocatalytic structures. The historical development of stability concepts, their realization and recent advances are described. Examples are presented that span the time from the inception of photoelectrochemical energy conversion to present day's renewed interest in storable solar energy. The application of (photo)corrosion proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…However calculations by Lewerenz show that the charge transfer was probably not due to a Poole-Frenkel type mechanism. 162 While the Lewis group has shown amorphous 'Leaky' TiO 2 to be highly conductive to charge, the McIntyre's group has shown that their amorphous TiO 2 creates a barrier for conduction of charge. 148 While both their ALD processes appear quite similar, small difference must account for the discrepancies and further studies are needed to clarify this situation.…”
Section: One Of the Mor E Interesting Follow Up Work On The Leaky Timentioning
confidence: 99%
“…However calculations by Lewerenz show that the charge transfer was probably not due to a Poole-Frenkel type mechanism. 162 While the Lewis group has shown amorphous 'Leaky' TiO 2 to be highly conductive to charge, the McIntyre's group has shown that their amorphous TiO 2 creates a barrier for conduction of charge. 148 While both their ALD processes appear quite similar, small difference must account for the discrepancies and further studies are needed to clarify this situation.…”
Section: One Of the Mor E Interesting Follow Up Work On The Leaky Timentioning
confidence: 99%
“…III-V compounds, like GaAs, also go through corrosion reactions (see Eq. 2) due to either accumulation of a large surface hole concentration in the dark or light illumination, generating holes at the surface (Lewerenz, 2014). However, p-type III-arsenide semiconductors have shown remarkable stability under conditions where an As 0 enriched surface provides passivation against corrosion (Young et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the applicationo fp rotectivef ilms, nanoparticles, and fusiblea lloys at the SC-electrolytei nterface are often used to enhance the durability and robustness of SCs that are prone to photocorrosion. [8][9][10][11] Generally,t he photocorrosion of SCs immersed in liquid electrolytes is studied on the basis of thermodynamic aspects, by comparing the quasi-Fermi levels of chargec arrierst ot he decomposition potentials of the SC. [12,13] Pourbaixd iagrams can also be used to investigate the stability and phase composition of the SCs at differentp otentials and pH.…”
Section: Introductionmentioning
confidence: 99%